2011
DOI: 10.1261/rna.2603911
|View full text |Cite
|
Sign up to set email alerts
|

Networking in a global world: Establishing functional connections between neural splicing regulators and their target transcripts

Abstract: Recent genome-wide analyses have indicated that almost all primary transcripts from multi-exon human genes undergo alternative pre-mRNA splicing (AS). Given the prevalence of AS and its importance in expanding proteomic complexity, a major challenge that lies ahead is to determine the functional specificity of isoforms in a cellular context. A significant fraction of alternatively spliced transcripts are regulated in a tissue-or cell-type-specific manner, suggesting that these mRNA variants likely function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 198 publications
(247 reference statements)
1
59
0
Order By: Relevance
“…Our data analysis identified a cluster of RBPs that are expressed in both brain and in human islets. This cluster includes members of the Elavl, Nova, and Rbfox families, which have been implicated in neuronal physiology and disease (28,(31)(32)(33)(34)(35). We found that Elavl4 and Nova2 are required for beta cell survival, and their depletion leads to activation of the intrinsic pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 77%
“…Our data analysis identified a cluster of RBPs that are expressed in both brain and in human islets. This cluster includes members of the Elavl, Nova, and Rbfox families, which have been implicated in neuronal physiology and disease (28,(31)(32)(33)(34)(35). We found that Elavl4 and Nova2 are required for beta cell survival, and their depletion leads to activation of the intrinsic pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 77%
“…Individual tissues differ in their alternative splicing patterns due to different expression levels of key SFs, which determine such patterns through a combinatorial mode of action (Singh and ValcĂĄrcel 2005;Calarco et al 2011). For example, members of the arginine-serine rich (SR) proteins and heterogenous nuclear ribonucleoproteins (hnRNPs) compete for splice-site regulatory elements (Eperon et al 2000;Smith and ValcĂĄrcel 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the pE1.3/3 and pE1.3/2/3 transcripts were most highly expressed in the kidney followed by the small intestine and then the liver, whereas the pE1.3/2/2.1/3 transcript was most highly expressed in the kidney followed by the liver, and was absent from the small intestine. Tissuespecific splicing, which incorporates up to eight different types of alternative splicing events (Wang et al 2008), has been extensively analyzed using microarrays in budding yeast and metazoans and using RNA-seq in human cell lines and tissues (Calarco et al 2011). Our data indicate an even more complicated level of mRNA splicing for the pPRLR gene, where the final mRNA composition not only depends on which tissue the transcript is expressed in but also on which first exon is transcribed.…”
Section: Figure 11mentioning
confidence: 89%